Self-frequency-doubling of ultrafast laser inscribed neodymium doped yttrium aluminum borate waveguides - Dong, Ningning (2011)
Buried channel optical waveguides, supporting orthogonal polarizations, have been fabricated in aneodymium doped yttrium aluminum borate nonlinear laser crystal by ultrafast laser inscription following the so-called “double line” approach. Confocal fluorescence and second harmonic imaging experiments have revealed that the original fluorescence and nonlinear properties have been not deteriorated by the waveguide inscription procedure. Preliminary laser experiments have shown the ability of the fabricated structures for green laser light generation under 808 nm optical pumping by self-frequency-doubling of the 1.06 um laser line of neodymium ions.